Systemic Sequential Therapy of CisGem, Tislelizumab, and Lenvatinib for Advanced Intrahepatic Cholangiocarcinoma Conversion Therapy - Ding, Yuan; Han, Xin; Sun, Zhongquan; Tang, Jinlong; Wu, Yingsheng; Wang, Weilin (Frontiers in Oncology, 2021)
Intrahepatic cholangiocarcinoma (CCA), always diagnosed at an advanced stage in recent years, is of high aggression and poor prognosis. There is no standard treatment beyond first-line chemotherapy and no molecular-targeted agents or immune checkpoint inhibitors approved for advanced intrahepatic CCA. Hence, we firstly report an original therapeutic strategy for a 60-year-old patient diagnosed with intrahepatic CCA categorized as Stage IIIB (T3N1M0) by the American Joint Committee on Cancer staging system. After histopathological examination and next-generation sequencing, the patient was treated with four courses of novel systemic sequential therapy (intravenous gemcitabine 1,000 mg/m2 and cisplatin 25 mg/m2 on days 1 and 8; oral lenvatinib 8 mg/day from days 1 to 21; intravenous tislelizumab 200 mg on day 15). Then, the patient achieved partial response and was operated on right hemihepatectomy, cholecystectomy, and abdominal lymph node dissection. Without any perioperative complications, the patient was discharged from our hospital in perfect condition. Thereafter, the patient continued to use this new regimen 1 month after surgery for adjuvant therapy and was confirmed without recurrence when we followed up. In a word, we found an effective therapeutic regimen for preoperative advanced intrahepatic CCA conversion therapy, which may become a new approach in cancer treatment in the future.